Restaurant resilience: A qualitative study of resilience, adaptability, and innovation of the Alabama restaurant industry during the COVID-19 pandemic - Mark Traynor; Emmanuella Owens; Sorcha O'Neill; Imran Rahman (Journal of Innovation & Knowledge)
The COVID-19 pandemic had a profound impact on the restaurant industry in Alabama. This qualitative study examines how Alabama restaurants demonstrated resilience and adaptability across three distinct phases of the pandemic, including the period of unrestricted activities, offering a new perspective. The findings highlight significant operational, financial, and labor-related difficulties faced during these phases. Key strategies include operational adjustments, technology integration, and strategic financial management. The study underscores the critical role of technology in maintaining customer connections and adapting service models during disruptions. It introduces a conceptual model that offers valuable contingency plans for operational innovation and resilience, helping restaurants manage crises effectively. Additionally, the research emphasizes the crucial role of government financial support in the survival and recovery of restaurants during the pandemic. The study enriches the existing literature by providing insights into the post-recovery impact of COVID-19 on the restaurant sector.